A master curve approach to model short- and long-term time-dependent nonlinear behavior of polyethylene. Issue 26 (26th October 2022) - Kühl, Andre; Polak, Maria Anna
Abstract: This paper presents a new approach for modeling the constitutive behavior of time-dependent materials by applying two phenomenological constitutive models to creep curves. Data obtained from short-term test are used for predicting the long-term behavior. The nonlinear viscoelastic response is modeled by using the multi-Kelvin model and the viscoplastic behavior is described by a power law. The methodology proposed herein for obtaining the constitutive formulation is based on developing master curves. Results obtained for polyethylene are discussed and compared using creep tests at different stress levels and has proved to be reliable based on the results analyzed in this work.